Sexuelle Vielfalt und die UnOrdnung der Geschlechter: Beiträge zur Soziologie der Sexualität - Koppetsch, Cornelia; Lewandowski, Sven (transcript, 2015)
Sexual diversity has been a central societal topic since the 1980s. Many taboos have been lifted, and sexual conduct has become more peaceful, more tolerant, and less authoritarian. But how diverse is sexuality really, and what role do gender relations play in this? through different topis such as sexual intimacy, couple sexuality, seduction, swinger clubs, prostitution, bisexuality, and transgender, the contributions to this volume show how sexual reality is construed in concrete everyday practice and which regulations it underlies through the societal order of the genders.